Structural features of subchondral bone cysts and adjacent tissues in hip osteoarthritis. Issue 8 (August 2022) - Nakasone, A.; Guang, Y.; Wise, A.; Kim, L.; Babbin, J.; Rathod, S.; Mitchell, A.J.; Gerstenfeld, L.C.; Morgan, E.F.
Summary: Objective: Focal lesions within the subchondral bone, termed subchondral bone cysts (SBCs), are clinically accepted radiographic markers of advanced osteoarthritis (OA), but their etiology in the hip is not well understood. Design: This study used micro-computed tomography (μCT), and histological and immunocytological analysis to examine the prevalence, size, location, and morphological and cellular features of SBCs found within 34 femoral heads (14 male, 20 female; age range = 43–80 years) obtained from total hip arthroplasty procedures. Results: SBCs were common—present in 91% of the femoral heads examined—and frequently commuted with the surface of the femoral head, but otherwise showed no preferred anatomical location. Few associations were found between SBC features and patient characteristics such as BMI, age and sex. SBCs were also heterogenous in composition, ranging from fibrous (most common) to predominantly fatty (least common) and often containing vasculature, nerve fibers, cartilage islands, and bony spicules. Despite this heterogeneity, focal abnormalities in bone density and cartilage thickness were consistently observed. Bone adjacent to SBCs was denser than that in the primary compressive group, and cartilage thickness in regions overlying SBCs was lower than in non-overlying regions. In contrast to these local bony changes, μCT-based finite element analyses indicated that the stiffness of the primary compressive group was only mildly affected by SBCs. Conclusions: These findings indicate that SBCs in the femoral head involve extensive perturbations in cellular activity, culminating in myriad skeletal tissue types and spatially heterogenous changes in bone and cartilage morphology that are likely to affect OA progression.